Impact of Infertility on Female Sexual Function. (1st August 2022) - Agarwal, N; Bachmann, G; Phillips, N
ABSTRACT: Introduction: Infertility, known to have a negative impact on couples, may cause significant distress in a relationship and can potentially lead to/or exacerbate sexual dysfunction. The physical, psychological, and often financial strains of infertility treatments, with potential failure to achieve the desired pregnancy can all contribute to this stress. Additionally, sex may be seen as becoming a medical or therapeutic act, with loss of spontaneity and pleasure. Hence, infertility and sexual dysfunction can be interlinked. Despite this association, intervention with effective templates of care appears to be limited in addressing this issue. Objective: A systematic literature review was done, focusing on female sexual dysfunction due to infertility and on what are available templates of care. Methods: A Google Scholar and pub med search were done with keywords "sexual dysfunction, " "infertility, " and "couple." Results: Although there are many studies depicting the correlation between the infertility and sexual dysfunction, templates of management appear to be lacking. Data suggest that infertility is a major contributor to female sexual dysfunction. That is, not only the infertility diagnosis but also the duration of infertility contributes to the sexual dysfunction. Studies have shown the lubrication and orgasm issues are the woman's main concerns. Also, sexual dysfunction is more profoundly impaired in patients with secondary infertility, lower educational level and higher partner education. Conclusions: These data suggest that couples undergoing infertility treatment should be evaluated for sexual dysfunction and be offered management during the infertility process. Sexual therapy does not appear to be routinely offered, despite the fact that these patients are at an increased risk of either developing a sexual dysfunction or a sexual dysfunction being exacerbated as a result of infertility as part of the infertility treatment process. Disclosure: No